Dimethyl ether synthesis on the admixed catalysts of Cu-Zn-Al-M (M = Ga, La, Y, Zr) and gamma-Al2O3: The role of modifier - Venugopal, Akula; Palgunadi, Jelliarko; Deog, Jung Kwang; Joo, Oh-Shim; Shin, Chae-Ho (ELSEVIER SCIENCE BV, 2009)
Dimethyl ether synthesis has been conducted on the admixed catalysts of Cu based catalysts (for methanol synthesis) and gamma-Al2O3 (for methanol dehydration). The Cu-Zn-Al-M (M=Ga, La, Y, Zr) hydrotalcite-like structures as catalyst precursors for methanol synthesis part of the admixed catalysts are synthesized by the co-precipitation method. The physico-chemical characteristics of the catalysts are analyzed by BET-surface area, XRD, TPR, SEM/EDS, XPS and N2O Pulse chemisorption studies. DME synthesis experiments showed that the CO conversion and DME yield are linearly correlated with Cu metal surface areas of Cu based catalysts admixed with gamma-Al2O3, indicating that methanol synthesis rate can control the overall DME synthesis rate. The yttrium-modified Cu-Zn-Al admixed catalysts showed the superior activity with a DME yield of 47.7% to other Cu-based catalysts. The reason may be attributed to the increase in Cu metal surface area by the addition of yttrium. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: METHANOL SYNTHESIS CATALYSTS; DME SYNTHESIS; OXIDE CATALYSTS; CONVERSION; CU/ZNO/AL2O3; REACTOR; SYNGAS; ACID; XPS